2022
DOI: 10.20535/2410-8286.254730
|View full text |Cite
|
Sign up to set email alerts
|

Development of Prospective Efl Teachers’ Questioning Skills in Classroom Discourse: Interdisciplinary Approach

Abstract: The research is devoted to the problem of mastering pre-service EFL teachers’ specific proficiency in using questions as an effective tool in the EL classroom discourse and university discourse. The purpose of the paper is to submit the teaching scheme of training pre-service EFL teachers’ questioning skills, encouraging them to work out their own teaching strategies in the future professional activity. The authors substantiate the possibility of improving MA students and pre-service EFL teachers’, questioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Another group of scientists [8] outline the ways of undergraduates' intercultural communicative competence developing, and propose recommendations for its building. T. Yeremenko et al [9] describe the learning scheme of intending teachers' questioning abilities formation, motivating them to the future professional activity. The researches show the possibility to improve undergraduates' communication skills and actualizing them during the theoreticalpractical course, and teaching practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another group of scientists [8] outline the ways of undergraduates' intercultural communicative competence developing, and propose recommendations for its building. T. Yeremenko et al [9] describe the learning scheme of intending teachers' questioning abilities formation, motivating them to the future professional activity. The researches show the possibility to improve undergraduates' communication skills and actualizing them during the theoreticalpractical course, and teaching practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The works of I. Zadorozhna & O. Datskiv (2022) and T. Yeremenko, I. Lukyanchenko, & A. Demchuk (2022) revealed that developing English communicative competence in education has a positive impact on the quality of future professional growth. Our research confirms the previous results (Liubashenko & Kornieva, 2019;Nykyporets & Ibrahimova, 2021) and proves that developing English speaking skills has positive impacts on educational and professional growth processes.…”
Section: Institutional Supportmentioning
confidence: 99%